Recovering corporate memory. Wine porters’ guilds and religious traditions in pre-industrial northern Italy - Laborda-Pemán, Miguel (Incontri. Rivista europea di studi italiani, 2016)
Review of: Lester K. Little, Indispensable immigrants: The wine porters of northern Italy and their saint, 1200-1800, Manchester, Manchester University Press, 2015, 229 p., ISBN: 978071909522, £ 70.00.